Game Theory and its Application in the analysis of Transportation sector in Iraq (Eurasian Journal of History, Geography and Economics, 2023)
This research aims at investigating whether private or public sectors are able to lead the transportation sector in Iraq. For this reason, the paper will apply the game theory and its participation to choose which of the competitors should lead. The research found that the private sector was more efficient in these activities that have a high level of profit like land, airways, and sea transportation and the public sector should leave these activities that have a low proportion of added value according to the capital formation, and constraint itself only to activities which give high level of profit.